2014
DOI: 10.2106/jbjs.m.00377
|View full text |Cite
|
Sign up to set email alerts
|

The Talar Body Prosthesis: Results at Ten to Thirty-six Years of Follow-up

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 6 publications
0
92
0
1
Order By: Relevance
“…Harnroongroj et al 14,15 introduced a stainless-steel talar body prosthesis designed by slit scanography and reported a postoperative median score of >75 points on the American Orthopaedic Foot & Ankle Society ankle-hindfoot scoring system. In contrast, we developed two models of custom-made artificial talar body implants made of alumina ceramic designed with computed tomography (CT) 16,17 .…”
mentioning
confidence: 99%
“…Harnroongroj et al 14,15 introduced a stainless-steel talar body prosthesis designed by slit scanography and reported a postoperative median score of >75 points on the American Orthopaedic Foot & Ankle Society ankle-hindfoot scoring system. In contrast, we developed two models of custom-made artificial talar body implants made of alumina ceramic designed with computed tomography (CT) 16,17 .…”
mentioning
confidence: 99%
“…In a subsequent report on the outcomes of talar body replacement with a metallic prosthesis by Harnroongroj and Harnroongroj [20], satisfactory function of the foot and ankle was observed during 10–36 years of follow-up. Angthong similarly reported that an anatomic metallic prosthesis provided satisfactory short-term follow-up outcomes for traumatic loss of the talus [21].…”
Section: Discussionmentioning
confidence: 99%
“…Stevens et al[17] even reported on a 14-year-old girl who underwent total talar replacement after an open talar dislocation. And again it was Harnroongroj to report on the largest series of 33 patients with by far the longest follow-up period of 10-36 years after implantation of a talar body prosthesis[15]. In this series published in 2014, 28 of the 33 prostheses were still in place at the time of final follow-up while five had failed prior to five years.…”
Section: Introductionmentioning
confidence: 99%
“…For example, early prosthesis failure occured as a result of size mismatch in two patients in the large series reported by Harnroongroj et al[15]. And according to Ando et al the procedure of total talar replacement carries at least a theoretical risk of anterior instability of the prosthesis, because the anterior talofibular ligament (ATFL) and deep deltoid ligaments are divided during the procedure[16].…”
Section: Introductionmentioning
confidence: 99%